Bacillus subtilis improves cotton photosynthetic traits and production by optimizing soil water-salt-nitrogen conditions under the brackish water irrigation - Yanpeng Bi; Beibei Zhou; Peiqi Ren; Shaoxiong Yao; Xiaopeng Chen; Yujiao Yang; Haobo Meng (Soil and Tillage Research, 2026)

Cordycepin inhibits human extravillous trophoblast invasion by suppressing snail-mediated MMP2 expression - Manman Guo; Siwei Luo; Beibei Bi; Xiaoyu Han; Yuanyuan Jia; Jung-Chien Cheng; Lanlan Fang (Tissue and Cell, 2026)

Probiotic Delivery Systems for Inflammatory Bowel Disease: Recent Advances and Translational Challenges - Haofan Liu; Lina Yang; Sicheng Huang; Yaqian He; Yinghua Xie; Yongshuai Jing; Beibei Hu; Zhongqiu Li; Haichao Bi; Zhiwei Li (Probiotics and Antimicrobial Proteins, 2026)

Acetaminophen overdose inhibits steroidogenic acute regulatory protein expression by reducing AKT-mediated SP1 expression in human granulosa-lutein cells - Jung-Chien Cheng; Qian Zhang; Lingling Zhang; Beibei Bi; Hailong Wang; Lanlan Fang; Hsun-Ming Chang; Ying-Pu Sun (Reproductive Toxicology, 2025)

Ground-based mobile imaging for detecting salt stress of cotton seedlings in the field - Jiayi Li; Peiqi Ren; Yanpeng Bi; Atoba Tolulope Opeyemi; Jie Cui; Yang Gao; Dapeng Ye; BeiBei Zhou; Haiyong Weng (Computers and Electronics in Agriculture, 2024)

Nutritional Metabolism of Antarctic Krill Product Protein in Rats - Xin Du; Beibei Xu; Yunqi Wen; Shijie Bi; Changhu Xue; Xiaoming Jiang (Journal of Ocean University of China, 2023)

Evaluation of Cd2+ stress on Synechocystis sp. PCC6803 based on single-cell elemental accumulation and algal toxicological response - Yao Tao; Man He; Beibei Chen; Gang Ruan; Pingping Xu; Yixue Xia; Gaofei Song; Yonghong Bi; Bin Hu (Aquatic Toxicology, 2023)

Improvement of solubility, gelation and emulsifying properties of myofibrillar protein from mantis shrimp (Oratosquilla oratoria) by phosphorylation modification under low ionic strength of KCl - Beibei Jia; Jinyu Chen; Gongru Yang; Jingyi Bi; Jinting Guo; Kun Shang; Siyang Wang; Zijian Wu; Kunsheng Zhang (Food Chemistry, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Occurrence and distribution of microplastics in coastal plain soils under three land-use types - De Bi; Beibei Wang; Zhu Li; Yabing Zhang; Xin Ke; Chengwang Huang; Wuxing Liu; Yongming Luo; Peter Christie; Longhua Wu (Science of The Total Environment, 2023)

Spatiotemporal development of land use systems, influences and climate variability in Southwestern Ghana (1970–2020) - Isaac Sarfo; Bi Shuoben; Li Beibei; Solomon Obiri Yeboah Amankwah; Emmanuel Yeboah; John Ernest Koku; Edward Kweku Nunoo; Clement Kwang (Environment, Development and Sustainability, 2022)

Observed and Coupled Model Intercomparison Project 6 multimodel simulated changes in near‐surface temperature properties over Ghana during the 20th century - Collins Oduro; Bi Shuoben; Brian Ayugi; Li Beibei; Hassen Babaousmail; Isaac Sarfo; Safi Ullah; Hamida Ngoma (International Journal of Climatology, 2022)
This article investigates seasonal and annual trends of near‐surface temperature (NST) during the last century (1901–2018) over Ghana. The ability of 24 global climate models (GCMs) from the sixth phase of the Coupled Model Intercomparison Project (CMIP6) to simulate abrupt mean temperature changes in Ghana from 1980 to 2014 was assessed. The trends' magnitude and abrupt changes were detected using Sen Slope Estimator (SSE) and sequential Mann–Kendall (SQMK) tests, respectively. Root mean square difference, correlation coefficient, and mean bias (B) were used to determine the skilfulness of GCMs in simulating NST relative to Climatic Research Unit (CRU TS4.04) datasets. Ghana's Southern belt is characterized by low temperatures, averaging 25°C to 27°C, whilst the northern belt is characterized by high temperatures (29–31°C). The inter‐annual variability of temperature over Ghana exhibits an increasing trend. Findings depict a significant increase in both the annual and seasonal temperatures of Tmin and Tmean, with a steady increase in Tmax. Results revealed the rate of increase had been higher in the country's northern regions (0.5°C) than in the south (0.3–0.4°C) in recent decades. The model performances for the interannual variability of annual and FMAM temperatures are better than their JJAS seasonal performances. The study's overall model ranking shows that Ghana's best performing models for annual, FMAM and JJAS seasons are INM‐CM5‐0, NorCPM1, and KACE‐1‐0‐G, respectively. Observations and comparisons provide useful reference values for a comprehensive assessment of various applications.

Modeling Nutrient Release in the Tai Lake Basin of China: Source Identification and Policy Implications - Beibei Liu; Heng Liu; Bing Zhang; Jun Bi (Environmental Management, 2013)

Relationship between gene polymorphisms of two cytokine genes (TNF-α and IL-6) and occurring of lung cancers in the ethnic group Han of China - Jing Liang; Xiaolin Liu; Zhenqiang Bi; Beibei Yin; Junjuan Xiao; Hairong Liu; Yan Li (Molecular Biology Reports, 2013)